Blood pressure distribution in relation with age, anthropometric measurements and socio economic status among school children of Warangal city, Telangana, India - Sirazuddin, Mohd; Farheen, Najma; Navley, Shirisha (International Journal of Contemporary Pediatrics, 2020)
Background: Hypertension is the one major global burden disease, causes 7.5 million deaths i.e.12.8%. Coronary Heart Disease Prevails 3-4% rural and 8-10% of urban population under 20 year’s age in India. Two fold rise in rural & six fold rise in urban areas since four decades. Environmental and Genetic factors i.e. Sex, BSA, obesity, family history of hypertension, dietary habits, physical activity, stress, race, ethnicity and socio economic status influence on children and adolescent. Many studies have established normal standards of BP for the children of different ages and races in their countries. Indian children cannot be adopted due to differences in ethnic, socio-economic, dietetic, environmental and emotional factors. Methods: A cross sectional study done with 2422 children of 5 to 16 years age school children, selected from 13 Schools (Government and Private) of Urban and Rural areas of Warangal. Results: A linear increase in mean BP with age, sex, weight, height, social status and locality. DBP has strong negative correlation with sex. i.e. female have high DBP and children of lower class and rural area has high DBP. 54 children <85th and 95th percentile and 5 children >95th percentile has comparatively high mean BP, 27 children with history of Hypertension in parents are >85th and 95th percentiles. Positive correlation with BMI in both sexes studied. A multivariate regression study confers positive strong correlation of Mean SBP and DBP with anthropometry. Conclusions: Observed similar results of SBP and DBP in both sexes, linear Increase in mean SBP and DBP with increasing age, weight, height and BMI. Family history of hypertension and high SES had direct correlation to SBP and DBP; class I SES has higher Mean SBP than class III SES.